Ultraviolet radiation resistant PBOH fiber and preparation method thereof
By introducing hydrogen bond structures into the molecular chain of PBO fibers and adopting copolymerization preparation method, the problems of PBO fiber aging and low compression strength under ultraviolet light are solved, and high-strength, ultraviolet radiation resistance and compression resistance are improved.
Patent Information
- Application Number
- CN202510007882.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-01-03
AI Technical Summary
PBO fiber ages rapidly under ultraviolet light, has a decline in mechanical properties, and has low compression strength, which limits its application in the field of advanced structural composite materials.
By introducing rich hydrogen bond structures such as O—H—O into the molecular chain of PBO fibers, and forming a high viscosity PBOH copolymer solution through copolymerization preparation method, followed by spinning and heat treatment to obtain high-strength ultraviolet irradiation PBOH fibers.
While maintaining high strength and high mode, the UV radiation resistance and compression resistance of PBO fibers are significantly improved. After 480 hours of ultraviolet aging, the tensile strength retention rate is as high as 81%.
Smart Images

Figure CN119593096A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer material processing, and specifically relates to the field of high-performance fiber modification, and further specifically relates to a high-strength radiation-resistant PBOH fiber and a preparation method thereof. Background Art
[0002] PBO (poly(p-phenylene benzobisoxazole)) fiber is a high-performance organic fiber with a tensile strength of up to 5.8GPa and a modulus of 280GPa, which is almost twice that of high-performance Kevlar fiber. In addition, under an inert atmosphere, the thermal decomposition temperature of PBO fiber is as high as 650℃, and it can be used for a long time at 300℃. The limiting oxygen index (LOI) of PBO fiber is 68, and it has excellent comprehensive performance and is known as the "king of fibers". PBO fiber has broad application prospects in aerospace, fire and bulletproof fields. Its excellent performance mainly depends on the rigid conjugated polymer main chain between benzobisoxazole and benzene ring. This structure produces π electron delocalization and resonance effect, making the PBO fiber structure extremely stable.
[0003] Nevertheless, like most aromatic heterocyclic fibers, PBO fibers also have the fatal defect of being not resistant to ultraviolet radiation. Under ultraviolet light irradiation, the aging process of PBO fibers is rapid, and the mechanical properties drop sharply, which greatly limits the application of PBO fibers. Therefore, the research on the modification of PBO fibers for ultraviolet light aging resistance has always been a research hotspot. At present, the modification of PBO fibers for ultraviolet light aging resistance mainly focuses on methods such as in-situ blending / copolymerization and fiber surface coating modification. Improving the ultraviolet light resistance of PBO fibers by in-situ blending / copolymerization has always been a research focus. For example, CN 101906677 A discloses a method for preparing PBO fibers resistant to ultraviolet light aging: passing the PBO spinning solution through a coagulation bath containing an antioxidant, and obtaining a high modulus PBO fiber containing an antioxidant by drying, winding and heat treatment. The fiber has long-lasting anti-aging properties, but the repeatability is low. In contrast, the fiber surface coating modification operation is simple and fast. For example, CN 102277726 A discloses a method for anti-ultraviolet aging of poly(p-phenylene benzobisoxazole) fibers: preparing an anti-ultraviolet aging mixed solution containing an anti-ultraviolet agent, a coupling agent, an acidic medium and a promoter, and forming a uniform anti-ultraviolet aging gel coating of 0.02 to 0.05 mm on the surface of the PBO fiber with the assistance of ultrasonic oscillation, thereby achieving ultraviolet protection of the PBO fiber. This method does not change the internal structure of PBO, but the modification will cause irreversible damage to the fiber surface, resulting in reduced fiber strength. In addition, the coating's ultraviolet resistance is not stable enough. As time goes on, substances such as ultraviolet absorbers gradually disappear, and the ultraviolet resistance of PBO will also decrease. In addition, CN202410497552.1 also discloses a method for directly improving the UV resistance of PBO fibers by heat treatment. The study believes that after a short-term treatment at a temperature of 600-700°C, a chromophore C=O and an auxiliary color group NH conjugated with the benzene ring are produced in the PBO fiber structure, so the ultraviolet spectrum is red-shifted more, and the original B-band absorption is red-shifted from about 400nm to nearly 500nm, but this treatment method greatly reduces the initial strength of the PBO fiber.
[0004] At the same time, compared with aramid fiber, PIPD fiber, graphite fiber and aromatic ester fiber, PBO fiber also has the weakness of low compressive strength. Analysis shows that this performance defect is mainly caused by the "inert" structure of PBO fiber. Due to the lack of polar groups such as hydroxyl and amine groups on the PBO molecular chain, PBO molecules cannot form intramolecular and intermolecular hydrogen bonds, and the interaction force between microfibers is weak, which makes PBO fibers easy to buckle and deform when bearing axial compressive stress, causing microfiber peeling and damage, thereby restricting the application of PBO fibers in the field of advanced structural composite materials. Researchers usually introduce hydroxyl groups on the PBO molecular chain to form a hydrogen bond structure inside the fiber to improve the compression resistance. However, this method usually destroys the regularity of PBO fibers due to the introduction of a third monomer, resulting in a decrease in the mechanical properties of PBO fibers.
[0005] Therefore, developing PBO fibers with improved UV resistance and compression resistance can effectively expand the application of PBO fibers in the field of advanced structural composite materials. In particular, developing a simple and effective preparation method to simultaneously improve the UV resistance and compression resistance of PBO fibers is an urgent problem to be solved in the current PBO fiber research field. Summary of the invention
[0006] The present invention aims to provide a high-strength ultraviolet radiation-resistant PBOH fiber and a simple and efficient method for modifying PBO fibers to prepare high-strength ultraviolet radiation-resistant PBOH fibers, which can improve the ultraviolet radiation resistance and compression resistance of the PBO fibers while maintaining their high strength and high modulus.
[0007] The high-strength ultraviolet radiation-resistant PBOH fiber is characterized by having a molecular structure shown in Formula I: (Formula I) Among them: x is 100~140, y is 5~35.
[0008] The R1 is R 1-01( ) , R 1-02( ) , R 1-03( ) , R 1-04( ) , R 1-05( ) , R 1-06( ) , R 1-07( ) One of them.
[0009] The R2 is R 2-01( ) , R 2-02( ) , R 2-03( ) , R 2-04( ) , R 2-05( ) , R 2-06( ) , R 2-07( ) , R 2-08( ), R 2-09( ), R 2-10( ), R 2-11( ), R 2-12( ), R 2-13( ), R 2-14( ), R 2-15( ), R 2-16( ), R 2-17( ), R 2-18( ) One of them.
[0010] The present invention also claims to protect the application of the ultraviolet radiation resistant PBOH fiber in aerospace and in fireproof and bulletproof materials.
[0011] In the molecular structure of the high-strength radiation-resistant PBOH fiber, a large number of intramolecular and intermolecular hydrogen bond structures are formed on the oxazole ring, which has the effect of absorbing and shielding ultraviolet light.
[0012] The hydrogen bonds are O—H--N, O—H--F, O—H--O, N—H--F, and N—H--O on the imidazole ring and the oxazole ring.
[0013] The hydrogen bonds form relatively stable five-membered ring, six-membered ring and eight-membered ring structures on the imidazole ring and the oxazole ring.
[0014] The high-strength ultraviolet radiation-resistant PBOH fiber is prepared by copolymerization, comprising the following steps: Preparation of PBO oligomer solution: Under argon protection, 4,6-diaminoresorcinol hydrochloride, R2, phosphorus pentoxide, phosphoric acid, and stannous chloride are added to a reactor, the proportion of phosphorus pentoxide in phosphoric acid is controlled to be 83.5 wt%, the temperature is gradually increased to 80 °C, and stirred at a constant temperature for 2 to 8 h to remove hydrogen chloride; phosphorus pentoxide is added, and then the temperature is gradually increased to 100 to 120 °C, and the reaction is carried out for 4 to 10 h to obtain a PBO oligomer solution.
[0015] Preparation of R1-R2 oligomer solution: Under argon protection, R1 hydrochloride, R2, phosphorus pentoxide, phosphoric acid, and stannous chloride are added to a reactor, the proportion of phosphorus pentoxide in phosphoric acid is controlled to be 83.5 wt%, the temperature is gradually increased to 80°C, and stirred at a constant temperature for 2-8 h to remove hydrogen chloride; phosphorus pentoxide is added, and then the temperature is gradually increased to 100-150°C, and the reaction is carried out for 6-16 h to obtain a R1-R2 oligomer solution.
[0016] Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution are mixed. Then, under argon protection, the mixture is stirred, heated to 120-150°C, and reacted for 6-16 hours; then heated to 160-185°C, and reacted for 2-18 hours to obtain a high-viscosity PBOH copolymer solution.
[0017] Chain extension: The high viscosity PBOH copolymer solution is added into a twin-screw extruder reactor protected by argon for repolymerization at a reaction temperature of 185-195 °C for 0.1-3 h to obtain a polymer solution of a high molecular weight PBOH copolymer.
[0018] Spinning: The polymer solution of the high molecular weight PBOH copolymer is spun, washed and dried by dry-jet wet spinning to obtain PBOH primary fibers.
[0019] Heat treatment: The PBOH primary fiber is heat treated at a certain temperature, tension and draft ratio, and the heat treatment time is controlled to obtain high-strength radiation-resistant PBOH fiber.
[0020] In the molecular structure of the high-strength radiation-resistant PBOH fiber, a large number of intramolecular and intermolecular hydrogen bond structures are formed on the oxazole ring, which has the effect of absorbing and shielding ultraviolet light.
[0021] The hydrogen bonds are O—H--N, O—H--F, O—H--O, N—H--F, and N—H--O on the imidazole ring and the oxazole ring.
[0022] The hydrogen bonds form relatively stable five-membered ring, six-membered ring and eight-membered ring structures on the imidazole ring and the oxazole ring.
[0023] The heat treatment temperature is 300-550°C; the heat treatment channel time is 5s-10min; and the axial tension is 4-16N.
[0024] The high-strength ultraviolet radiation-resistant PBOH fiber prepared by the above preparation method has a tensile strength retention rate of up to 81% after ultraviolet aging for 480 hours.
[0025] The beneficial effects of the PBO modification method and PBOH structure proposed in the present invention are: 1) Through in-situ copolymerization modification, abundant O—H--O and other hydrogen bond structures are introduced into the PBO molecular chain, so that the molecular chain orientation structure in the PBO microfiber is regular and more stable, with higher tensile strength and greater modulus; 2) Introducing O—H--N hydrogen bond structures on both sides of the imidazole ring of the UV-sensitive structure of the PBO molecular chain greatly improves the UV radiation resistance of the imidazole ring, and the modification effect is long-lasting; 3) The intermolecular N-H--F hydrogen bonds are used to strengthen the intermolecular forces and significantly improve the compressive strength of PBO fibers; 4) This method has a simple process and is basically the same as the PBO fiber synthesis preparation process. It is easy to promote and is a very potential PBO fiber modification method with great practical value. It can be widely used in aerospace and military fields. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 : The molecular structure of PBOH-47 obtained in Example 1; Figure 2 : The hydrogen bond network structure in the PBOH-47 fiber obtained in Example 1; Figure 3 : XRD comparison diagram of PBOH-47 and PBO fibers obtained in Example 1; Figure 4 : Comparison of infrared spectra of PBOH-47 and PBO obtained in Example 1; Figure 5 : Comparison of XPS spectra of PBOH-47 and PBO fibers obtained in Example 1; Figure 6 : PBOH-47 and PBO fiber strength-ultraviolet irradiation time curves obtained in Example 1; Figure 7 : Surface morphology of the PBOH-47 fiber obtained in Example 1 after UV irradiation for different time periods; Figure 8 : Comparison of the compressive strength of PBOH and PBO fibers obtained in Example; Fig. 9 : Picture of PBOH-47 fiber obtained in Example 1. DETAILED DESCRIPTION
[0027] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only a part of the embodiments of the invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work belong to the protection scope of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the conventional conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially. Example
[0028] Preparation of PBO oligomer solution: Under argon protection, 4,6-diaminoresorcinol hydrochloride (21.3 g), R 2-09 (18.26 g), phosphorus pentoxide (56.73 g), phosphoric acid (93.43 g), and stannous chloride (1.1 g) were added into the reactor, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 8 h to remove hydrogen chloride; phosphorus pentoxide (23.92 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 115 °C, and the reaction was carried out for 6 h to obtain a PBO oligomer solution.
[0029] Preparation of R1-R2 oligomer solution: Under argon protection, 1-04 Hydrochloride (3.4 g), R 2-07 (6.552 g), phosphorus pentoxide (14.27 g), phosphoric acid (23.5 g), and stannous chloride (0.3 g) were added into the reaction kettle, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 6 h to remove hydrogen chloride; phosphorus pentoxide (6.02 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 140 °C, and the reaction was carried out for 15 h to obtain a R1-R2 oligomer solution.
[0030] Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution were mixed. Then, the mixture was stirred under argon protection, heated to 150 °C, and reacted for 12 h; then heated to 175 °C, and reacted for 16 h to obtain a high-viscosity PBOH copolymer solution.
[0031] Chain extension: The high viscosity PBOH copolymer solution was added into a twin-screw extruder reactor protected by argon for repolymerization at a reaction temperature of 190 °C for 1 h to obtain a polymer solution of a high molecular weight PBOH copolymer with a mass fraction of 14.5%.
[0032] Spinning: The polymer solution of the high molecular weight PBOH copolymer is spun, washed and dried by dry-jet wet spinning to obtain PBOH primary fibers.
[0033] Heat treatment: The PBOH primary fiber was heat treated at 350℃ and 10N tension for 2 min to obtain high-strength radiation-resistant PBOH-47 fiber. The fiber has a compressive strength of 0.65 GPa and a tensile strength of 5.6 GPa at room temperature. After 480 hours of ultraviolet irradiation, the tensile strength remains at 78%. Example
[0034] Preparation of PBO oligomer solution: Under argon protection, 4,6-diaminoresorcinol hydrochloride (21.3 g), R 2-09 (18.26 g), phosphorus pentoxide (51.01 g), phosphoric acid (79.11 g), and stannous chloride (0.9 g) were added into the reactor, and the temperature was gradually increased to 80 °C, and stirred at constant temperature for 2 h to remove hydrogen chloride; phosphorus pentoxide (20.36 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 120 °C, and the reaction was carried out for 4 h to obtain a PBO oligomer solution.
[0035] Preparation of R1-R2 oligomer solution: Under argon protection, 1-01 Hydrochloride (1.88 g), R 2-01 (2.178 g), phosphorus pentoxide (5.23 g), phosphoric acid (8.11 g), and stannous chloride (0.11 g) were added into the reaction kettle, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 8 h to remove hydrogen chloride; phosphorus pentoxide (2.09 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 100 °C, and the reaction was carried out for 6 h to obtain a R1-R2 oligomer solution.
[0036] Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution were mixed. Then, the mixture was stirred under argon protection, heated to 160 °C, and reacted for 17 h; then heated to 185 °C, and reacted for 2 h to obtain a high-viscosity PBOH copolymer solution.
[0037] Chain extension: The high viscosity PBOH copolymer solution was added into a twin-screw extruder reactor protected by argon for repolymerization at a reaction temperature of 185 °C for 0.1 h to obtain a polymer solution of a high molecular weight PBOH copolymer with a mass fraction of 16%.
[0038] Spinning: The polymer solution of the high molecular weight PBOH copolymer is spun, washed and dried by dry-jet wet spinning to obtain PBOH primary fibers.
[0039] Heat treatment: The PBOH as-spun fiber was heat treated at 550℃ and 16N tension for 5 seconds to obtain high-strength radiation-resistant PBOH-11 fiber. The fiber has a compressive strength of 0.33 GPa and a tensile strength of 5.3 GPa at room temperature. After 480 hours of ultraviolet irradiation, the tensile strength remains at 76%. Example
[0040] Preparation of PBO oligomer solution: Under argon protection, 4,6-diaminoresorcinol hydrochloride (21.3 g), R 2-09 (18.26 g), phosphorus pentoxide (52.47 g), phosphoric acid (103.45 g), and stannous chloride (0.92 g) were added into the reactor, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 8 h to remove hydrogen chloride; phosphorus pentoxide (34.76 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 120 °C, and the reaction was carried out for 10 h to obtain a PBO oligomer solution.
[0041] Preparation of R1-R2 oligomer solution: Under argon protection, 1-02 Hydrochloride (0.7 g), R 2-04 (1.012 g), phosphorus pentoxide (2.27 g), phosphoric acid (4.48 g), and stannous chloride (0.24 g) were added into the reaction kettle, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 4 h to remove hydrogen chloride; phosphorus pentoxide (1.5 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 150 °C, and the reaction was carried out for 16 h to obtain a R1-R2 oligomer solution.
[0042] Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution were mixed. Then, the mixture was stirred under argon protection, heated to 140 °C, and reacted for 10 h; then heated to 185 °C, and reacted for 18 h to obtain a high-viscosity PBOH copolymer solution.
[0043] Chain extension: The high viscosity PBOH copolymer solution was added into a twin-screw extruder reactor protected by argon for repolymerization at a reaction temperature of 195 °C for 0.1 h to obtain a polymer solution of a high molecular weight PBOH copolymer with a mass fraction of 13%.
[0044] Spinning: The polymer solution of the high molecular weight PBOH copolymer is spun, washed and dried by dry-jet wet spinning to obtain PBOH primary fibers.
[0045] Heat treatment: The PBOH primary fiber was heat treated at 300℃ and 16N tension for 1 min to obtain high-strength radiation-resistant PBOH-24 fiber. The fiber has a compressive strength of 0.45 GPa and a tensile strength of 5.2 GPa at room temperature. After 480 hours of ultraviolet irradiation, the tensile strength remains at 81%. Example
[0046] Preparation of PBO oligomer solution: Under argon protection, 4,6-diaminoresorcinol hydrochloride (21.3 g), R 2-09 (18.26 g), phosphorus pentoxide (41.88 g), phosphoric acid (89.22 g), and stannous chloride (0.98 g) were added into the reactor, and the temperature was gradually increased to 80 °C, and stirred at the constant temperature for 5 h to remove hydrogen chloride; phosphorus pentoxide (34.71 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 110 °C, and the reaction was carried out for 7 h to obtain a PBO oligomer solution.
[0047] Preparation of R1-R2 oligomer solution: Under argon protection, 1-03 Hydrochloride (2.76 g), R 2-06 (5.236 g), phosphorus pentoxide (8.46 g), phosphoric acid (18.03 g), and stannous chloride (0.22 g) were added into the reaction kettle, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 5 h to remove hydrogen chloride; phosphorus pentoxide (7.01 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 130 °C, and the reaction was carried out for 14 h to obtain a R1-R2 oligomer solution.
[0048] Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution were mixed. Then, the mixture was stirred under argon protection, heated to 140 °C, and reacted for 12 h; then heated to 165 °C, and reacted for 18 h to obtain a high-viscosity PBOH copolymer solution.
[0049] Chain extension: The high viscosity PBOH copolymer solution was added into a twin-screw extruder reactor protected by argon for repolymerization at a reaction temperature of 185 °C for 3 h to obtain a polymer solution of a high molecular weight PBOH copolymer with a mass fraction of 15%.
[0050] Spinning: The polymer solution of the high molecular weight PBOH copolymer is spun, washed and dried by dry-jet wet spinning to obtain PBOH primary fibers.
[0051] Heat treatment: The PBOH primary fiber was heat treated at 450℃ and 4 N tension for 5 min to obtain high-strength radiation-resistant PBOH-36 fiber. The fiber has a compressive strength of 0.39 GPa and a tensile strength of 5.1 GPa at room temperature. After 480 hours of ultraviolet irradiation, the tensile strength remains at 69%. Example
[0052] Preparation of PBO oligomer solution: Under argon protection, 4,6-diaminoresorcinol hydrochloride (21.3 g), R 2-09 (18.26 g), phosphorus pentoxide (54.55 g), phosphoric acid (87.96 g), and stannous chloride (0.9 g) were added into the reactor, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 8 h to remove hydrogen chloride; phosphorus pentoxide (23.23 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 100 °C, and the reaction was carried out for 4 h to obtain a PBO oligomer solution.
[0053] Preparation of R1-R2 oligomer solution: Under argon protection, 1-05 Hydrochloride (2.09 g), R 2-02 (2.376 g), phosphorus pentoxide (6.16 g), phosphoric acid (9.93 g), and stannous chloride (0.21 g) were added into the reaction kettle, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 8 h to remove hydrogen chloride; phosphorus pentoxide (2.62 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 150 °C, and the reaction was carried out for 16 h to obtain a R1-R2 oligomer solution.
[0054] Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution were mixed. Then, the mixture was stirred under argon protection, heated to 150 °C, and reacted for 12 h; then heated to 185 °C, and reacted for 18 h to obtain a high-viscosity PBOH copolymer solution.
[0055] Chain extension: The high viscosity PBOH copolymer solution was added into a twin-screw extruder reactor protected by argon for repolymerization at a reaction temperature of 195 °C for 3 h to obtain a polymer solution of a high molecular weight PBOH copolymer with a mass fraction of 14.8%.
[0056] Spinning: The polymer solution of the high molecular weight PBOH copolymer is spun, washed and dried by dry-jet wet spinning to obtain PBOH primary fibers.
[0057] Heat treatment: The PBOH as-spun fiber was heat treated at 550℃ and 9 N tension for 0.5 min to obtain high-strength radiation-resistant PBOH-52 fiber. The fiber has a compressive strength of 0.42 GPa and a tensile strength of 5.4 GPa at room temperature. After 480 h of ultraviolet irradiation, the tensile strength remains at 73%. Example
[0058] Preparation of PBO oligomer solution: Under argon protection, 4,6-diaminoresorcinol hydrochloride (21.3 g), R 2-09 (18.26 g), phosphorus pentoxide (61.84 g), phosphoric acid (102.92 g), and stannous chloride (1.15 g) were added into the reactor, and the temperature was gradually increased to 80 °C, and stirred at the constant temperature for 6 h to remove hydrogen chloride; phosphorus pentoxide (24.13 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 100 °C, and the reaction was carried out for 4 h to obtain a PBO oligomer solution.
[0059] Preparation of R1-R2 oligomer solution: Under argon protection, 1-07 Hydrochloride (4.75 g), R 2-08 (6.048 g), phosphorus pentoxide (16.88 g), phosphoric acid (28.09 g), and stannous chloride (0.27 g) were added into the reaction kettle, and the temperature was gradually increased to 80 °C, and stirred at a constant temperature for 8 h to remove hydrogen chloride; phosphorus pentoxide (6.59 g) was added to control the proportion of phosphorus pentoxide in phosphoric acid to 83.5 wt%, and then the temperature was gradually increased to 100 °C, and the reaction was carried out for 12 h to obtain a R1-R2 oligomer solution.
[0060] Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution were mixed. Then, the mixture was stirred under argon protection, heated to 150 °C, and reacted for 12 h; then heated to 165 °C, and reacted for 16 h to obtain a high-viscosity PBOH copolymer solution.
[0061] Chain extension: The high viscosity PBOH copolymer solution was added into a twin-screw extruder reactor protected by argon for repolymerization at a reaction temperature of 185 °C for 2.5 h to obtain a polymer solution of a high molecular weight PBOH copolymer with a mass fraction of 13.6%.
[0062] Spinning: The polymer solution of the high molecular weight PBOH copolymer is spun, washed and dried by dry-jet wet spinning to obtain PBOH primary fibers.
[0063] Heat treatment: The PBOH as-spun fiber was heat treated at 300°C and 16 N tension for 10 min to obtain high-strength radiation-resistant PBOH-78 fiber. The fiber has a compressive strength of 0.37 GPa and a tensile strength of 5.3 GPa at room temperature. After 480 h of ultraviolet irradiation, the tensile strength remains at 54%.
[0064] Preferably, R1-04 and R2-07 are used as comonomers of PBO polymer to obtain PBOH molecular structure, as shown in the attached Figure 1 The PBOH fiber has a rich hydrogen bond network of O—H--N, O—H--F, O—H--O, N—H--F, N—H—O, etc., as shown in the attached Figure 2 shown.
Claims
1. A UV-resistant PBOH fiber, characterized in that: It has a molecular structure shown in Formula I: (Formula I) Among them: x is 100~140, y is 5~35; The R1 is R 1-01( ) , R 1-02( ) , R 1-03( ) , R 1-04( ) , R 1-05( ) , R 1-06( ) , R 1-07( ) One of; R2 is R 2-01( ) , R 2-02( ) , R 2-03( ), R 2-04( ) , R 2-05( ) , R 2-06( ) , R 2-07( ) , R 2-08( ), R 2-09( ), R 2-10( ), R 2-11( ), R 2-12( ), R 2-13( ), R 2-14( ), R 2-15( ), R 2-16( ), R 2-17( ), R 2-18( ) One of them.
2. Use of the ultraviolet radiation resistant PBOH fiber according to claim 1 in aerospace or in fireproof and bulletproof materials.
3. The method for preparing the ultraviolet radiation resistant PBOH fiber according to claim 1, characterized in that: The copolymerization preparation method comprises the following steps: Preparation of PBO oligomer solution: under argon protection, 4,6-diaminoresorcinol hydrochloride, R2, phosphorus pentoxide, phosphoric acid, and stannous chloride are added to a reaction kettle, and the temperature is gradually increased to 80°C, and stirred at a constant temperature for 2-8 hours to remove hydrogen chloride; phosphorus pentoxide is added, and then the temperature is gradually increased to 100-120°C, and the reaction is carried out for 4-10 hours to obtain a PBO oligomer solution; Preparation of R1-R2 oligomer solution: under argon protection, add R1 hydrochloride, R2, phosphorus pentoxide, phosphoric acid, and stannous chloride into a reaction kettle, gradually increase the temperature to 80°C, stir at constant temperature for 2-8 hours, remove hydrogen chloride; add phosphorus pentoxide, then gradually increase the temperature to 100-150°C, react for 6-16 hours, and obtain R1-R2 oligomer solution; Copolymerization of PBO and R1-R2 oligomers: Under argon protection, the PBO oligomer solution and the R1-R2 oligomer solution are mixed; then stirred under argon protection, the temperature is raised to 120-150°C, and the reaction is carried out for 6-16 hours; then the temperature is raised to 160-185°C, and the reaction is carried out for 2-18 hours to obtain a high-viscosity PBOH copolymer solution; Chain extension: adding the high viscosity PBOH copolymer solution into a twin-screw extruder reactor protected by argon to carry out repolymerization at a reaction temperature of 185-195°C for 0.1-3 h to obtain a polymer solution of a high molecular weight PBOH copolymer; Spinning: Spinning, washing and drying the polymer solution of the high molecular weight PBOH copolymer by dry-jet wet spinning to obtain PBOH primary fibers; Heat treatment: The PBOH primary fiber is heat treated at a certain temperature, tension and draft ratio, and the heat treatment time is controlled to obtain radiation-resistant PBOH fiber.
4. The method for preparing ultraviolet radiation resistant PBOH fiber according to claim 3, characterized in that: The heat treatment temperature is 300-550°C.
5. The method for preparing ultraviolet radiation resistant PBOH fiber according to claim 3, characterized in that: The time of heat treatment channel is 5s-10min.
6. The method for preparing ultraviolet radiation resistant PBOH fiber according to claim 3, characterized in that: The tension is 4~16N.
7. The method for preparing ultraviolet radiation resistant PBOH fiber according to claim 3, characterized in that: In steps (1) and (2), the proportion of phosphorus pentoxide in phosphoric acid is controlled to be 83.5 wt%.
8. The ultraviolet radiation resistant PBOH fiber prepared by the preparation method of claim 3, characterized in that: After being aged by ultraviolet light for 480 hours, the tensile strength retention rate of the radiation-resistant PBOH fiber is as high as 81%.
Citation Information
Patent Citations
Preparation method of anti-ultraviolet aging polyphenylene benzodioxazole fiber
CN101906677A
A method for resisting UV aging of poly(p-phenylenebenzodioxazole) fibers
CN102277726A
Ultraviolet resisting PBO fibre and preparing method thereof
CN101215732A
Method for preparing anti-ultraviolet ageing poly-p-phenylene-benzobisoxazole (PBO) fiber
CN101397696A
Preparation method for ultraviolet-resistant PBO fibers
CN103160950A